MODERN METHODS OF PRESERVING BREAST FEEDING IN CHILDREN OF THE FIRST MONTHS OF LIFE WITH HEALTH DISORDERS - T. V. Turti; L. S. Namazova-Baranova; I. A. Belyaeva; E. P. Zimina; S. B. Lazurenko; M. D. Mitish; E. A. Bakovich; M. S. Rtichsheva; N. Y. Savvateeva (Педиатрическая фармакология, 2014)
The issue of preserving and prolonging breast feeding is relevant for many countries around the world. It is especially relevant in premature infants and the children born with various perinatal pathologies. Scientific literature features the primary reasons of weaning: work activity resumption by nursing mothers, milk deficiency, breast refusal, insufficient awareness of mothers. The article presents results of two studies performed at the Scientific Center of Children’s Health. Results of a medical-psychological-pedagogical questioning of 85 mothers of premature infants demonstrate insufficient work of medical personnel in the sphere of preserving breast feeding in whole and in the children born with perinatal pathologies in particular; and the need of young women and their families in obtaining information on the benefits of breast feeding, training and assistance in the course of parental performance. The study resulted in formulation of recommendations on breast feeding support. It is important to establish the possibility to return to full breast feeding after enforced weaning and in the event of supplementary/mixed feeding. Results of the second study (n = 33) demonstrated that the use of special medical devices (pacifiers, feeding bottles) developed on the basis of thorough research in the sphere of maternal breast sucking physiology in natural feeding termination risk group children helps to preserve children’s need therein and ensures efficient return of children to maternal breast feeding.